Harnessing The Open Science Infrastructure For An Efficient African Response To Covid-19 [Preprint] - Havemann, Jo; Bezuidenhout, Louise; Achampong, Joyce; Akligoh, Harry; Ayodele, Obasegun; Hussein, Shaukatali; Ksibi, Nabil; Mboa Nkoudou, Thomas Hervé; Obanda, Johanssen; Owango, Joy; Sanga, Valerian Linus1; Stirling, Julian; et al. (My University, 2020)
We are seeking feedback and further input on this preprint manuscript. Go to outbreaksci.prereview.org/10.5281/zenodo.3733767 to leave a review. Please note: This document in its current preprint version (v1.0) is open for comments. Please make direct suggestions to the text at tinyurl.com/Open-Science-Africa-COVID-19, or email the corresponding authors. To contribute in the collaborative response in some of the work steps and/or financially, please visit https://info.africarxiv.org/contribute/.
Keywords: Open Science infrastructure; COVID-19; African response